Concerted nucleophilic aromatic substitution with (19)F(−) and (18)F(−) - Neumann, Constanze N. (Nature, 2016)
Nucleophilic aromatic substitution (S(N)Ar) is widely used by organic chemists to functionalize aromatic molecules, and it is the most commonly used method to generate arenes that contain a (18)F for use in PET imaging.(1) A wide range of nucleophiles exhibit S(N)Ar reactivity, and the operational simplicity of the reaction means that the transformation can be conducted reliably and on large scales.(2) During S(N)Ar, attack of a nucleophile at a carbon atom bearing a ‘leaving group’ leads to a negatively charged intermediate called a Meisenheimer complex. Only arenes with electron-withdrawing substituents can sufficiently stabilize the resulting build-up of negative charge during Meisenheimer complex formation, limiting the scope of S(N)Ar reactions: the most common S(N)Ar substrates contain strong π-acceptors in the ortho and/or para position(s).(3) In this manuscript, we present an unusual concerted nucleophilic aromatic substitution reaction (CS(N)Ar) that is not limited to electron-poor arenes, because it does not proceed via a Meisenheimer intermediate. We show a phenol deoxyfluorination reaction for which CS(N)Ar is favored over a stepwise displacement. Mechanistic insights enabled us to develop a functional group–tolerant (18)F-deoxyfluorination reaction of phenols, which can be used to synthesize (18)F-PET probes. Selective (18)F introduction, without the need for the common, but cumbersome, azeotropic drying of (18)F, can now be accomplished from phenols as starting materials, and provides access to (18)F-labeled compounds not accessible through conventional chemistry.